Analisis Kualitas Pelayanan pada CV Wasis Kota Banjarbaru - Chintia Meike; Sudirwo Sudirwo (Jurnal Ilmiah Ekonomi Bisnis, 2022)
The purpose of this study was to analyze the quality of service at CV Wasis Banjarbaru City. The method uses qualitative descriptive, where what is obtained becomes a description of the process carried out by CV Wasis doing business in the borehole business. The problems that exist in the company include delays in the repair process and the lack of quality service provided by employees. Data analysis techniques used interviews with employee informants CV Wasis Banjarbaru City as many as 9 people. The results showed that the quality of service at CV Wasis Banjarbaru City was not as expected, including employees who were not reliable in serving, less responsive, politeness was still lacking and the physical office was very untidy, not maintained and many facilities were outdated. So, what should be done to improve the quality of service can be training on how to properly serve customers, improve employee responsiveness and courtesy, and immediately replace and repair the physical office and facilities.